2011
DOI: 10.1083/jcb.201108081
|View full text |Cite
|
Sign up to set email alerts
|

Cell death and infection: A double-edged sword for host and pathogen survival

Abstract: Host cell death is an intrinsic immune defense mechanism in response to microbial infection. However, bacterial pathogens use many strategies to manipulate the host cell death and survival pathways to enhance their replication and survival. This manipulation is quite intricate, with pathogens often suppressing cell death to allow replication and then promoting it for dissemination. Frequently, these effects are exerted through modulation of the mitochondrial pro-death, NF-κB–dependent pro-survival, and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
248
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(258 citation statements)
references
References 102 publications
3
248
0
7
Order By: Relevance
“…Although it is recognized that pathogens can modulate programmed cell death pathways, including apoptosis, pyroptosis, and necroptosis (2,5), previous studies examining N. gonorrhoeae have focused primarily on the apoptosis pathway (17)(18)(19)21). In this study, we demonstrated that N. gonorrhoeae does not induce apoptosis in End/E6E7 cells as measured by changes in phosphatidylserine and caspase-3, confirming previous studies (21).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although it is recognized that pathogens can modulate programmed cell death pathways, including apoptosis, pyroptosis, and necroptosis (2,5), previous studies examining N. gonorrhoeae have focused primarily on the apoptosis pathway (17)(18)(19)21). In this study, we demonstrated that N. gonorrhoeae does not induce apoptosis in End/E6E7 cells as measured by changes in phosphatidylserine and caspase-3, confirming previous studies (21).…”
Section: Discussionsupporting
confidence: 78%
“…While repression of cell death pathways favors host cell survival, induction of cell death can be beneficial for pathogens. Accordingly, pathogens often manipulate such cell death pathways to favor their own replication and persistence (3)(4)(5). Apoptosis, pyroptosis, and necroptosis are programmed cell death pathways with distinct inflammatory outcomes; apoptosis is noninflammatory, while pyroptosis and necroptosis are highly inflammatory (6).…”
mentioning
confidence: 99%
“…The elimination of infected cells via apoptosis is an evolutionarily conserved defense mechanism (30). So it is not surprising that % fragmented nuclei…”
Section: Discussionmentioning
confidence: 99%
“…In response to intracellular bacterial infection, at least two major types of cell death might occur: pyroptosis and apoptosis (8,9). Through detection of bacterial components such as flagellin and the conserved inner rod protein of T3SS, infected macrophages are induced to assemble inflammasome complexes in which caspase-1 is activated.…”
mentioning
confidence: 99%